The Effect of Health Education on Providing Basic Life Support (BLS) on Knowledge and Attitudes of the Community in Pre-Hospital Treatment - Cahyono, Budi; S, Suyatno H; Wijaya, Siswanto Agung; Hidayat, Mohammad Kuntadi Syamsul (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2016)
Background: Basic Life Assistance is an emergency measure which is a clinical situation in which patients need immediate medical action to save lives and further disabilities (Law of the Republic of Indonesia number 44 concerning hospitals, 2009), And within a decade, technological developments and transportation are increasing rapidly, the high demands of the community also provide transportation services. The increased transportation services were not accompanied by an increase in people's knowledge and attitudes. Along with the development of transportation, there are also many community demands regarding adequate intra-road structures. However, until now, there are still many bad intra-structure roads managed by the government.Objective: to research the effect of health education on the provision of Basic Life Support (BHD) on public knowledge and attitudes on pre-hospital accidentsMethods: Pre-experimental design with one group pre-test-post test design.Results: There was an increase in good attitudes from before being given health education to people with good knowledge after being given education by 51.7%. Before being given Health Education a good public attitude was 6 (18.75%) and after being given health education a good public attitude was 18 (56.25%). There is an influence between Health Education on Knowledge and Community Attitudes on the handling of pre-hospital aid in the village of Sukorejo, Kec. Gandusari Kab. TrenggalekConclusion: There is an influence between Health Education on Knowledge and Community Attitudes on pre-hospital accidents in Sukorejo Village, Gandusari District, Trenggalek Regency.